Institutional Approach to Analysis and Formation of Control Systems of Subsidiary Business Processes of an Industrial Enterprise - Makhmutov, Ilnur Ilyazovich; Khuzina, Ekaterina Alexandrovna; Akhmetgareeva, Aysylu Amirzyanovna (International Journal of Criminology and Sociology, 2021)
At the junction of the XX-XXI centuries, an increasing number of leading managers and researchers in the field of management has identified the effectiveness of the management system as the most important factor in the organization's competitiveness, the main task of which is to make better and full use of the knowledge, experience and skills of the organization's staff. Overall, the main aim of the study is to investigate an Institutional approach to analysis and Formation of Control Systems of Subsidiary Business. Processes of an Industrial Enterprise As an analysis of individual and collective investments of individuals in financial markets, we will evaluate a set of the following factors: a list of professional intermediaries working with a certain investment object or instrument of collective investment, their position on the market and results of work, a set of offered services and products, investment conditions, dynamics of actual investments in this type of asset, its profitability, as well as dynamics of the market as a whole. Until the end of the 1980s, the main element determining the organization of work in enterprises was the function performed by the structural unit (for example, procurement, production, sales, etc.). Thus, the leading world companies had a functional organizational structure.